Jewish Immigrants in Israel: Disintegration Within Integration? - Desille, Amandine (2019)
In her chapter, ‘Disintegration within integration’, Amandine Desille examines more recent transformations of Israel’s Law of Return – the Israeli immigration policy which provides the (imagined) repatriation of Diaspora Jews to Israel – in a context of liberalisation of the Israeli economy and the devolution of power to local authorities. Today, new immigrants follow two paths of ‘integration’: ‘direct absorp-tion’, where immigrants are granted benefits while being free to settle wherever they find fit; and ‘community absorption’, where immigrants are placed in ‘absorption centres’ and see their entitlements conditioned by residence, religious observance and more. Those two paths are ‘ethnicised’ in the sense that they depend on country of origin – Western immigrants, considered as economically useful, benefit from direct absorption and a more pluralist attitude of local governments, while immi-grants from Africa and Asia are the objects of an assimilationist policy. This situa-tion of ‘(dis)integration’ within what is supposed to be an inclusive immigrant policy for all Jews, shows the extent to which new criteria of perceived economic performance limit the integration of specific segments of newcomers. The rescaling of immigration and immigrant policies to subnational governments, although it has introduced a more multicultural approach, antagonist to the assimilationist ideology at work in Israel, has not enabled an alternative policy framework which is more accommodating to all.